Simulation-Based Training and Nursing Documentation Competency in Community Health Centers: Pelatihan Berbasis Simulasi dan Kompetensi Dokumentasi Keperawatan di Puskesmas - Suwarto, Tri; Kartikasari, Fitriana; Purnomo, Jeki (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Accurate nursing documentation is essential for patient safety and service accountability in primary health care settings. Specific background: Community health centers frequently experience challenges due to limited documentation competence among nurses. Knowledge gap: Existing training approaches in these facilities rarely provide experiential learning that strengthens both theoretical understanding and practical skills. Aims: This study examined whether simulation-based training supports the development of knowledge and skills in nursing documentation among nurses in community health centers. Results: Using a two-group pre-test and post-test design with 46 participants, findings showed marked increases in documentation knowledge and clinical documentation skills among nurses who participated in the simulation training, while the control group showed minimal change. Novelty: The study provides empirical evidence in a primary care context showing that simulation-based training leads to substantial gains in documentation competence across multiple components of nursing practice. Implications: Integrating simulation-based learning into nurse development programs within community health centers can strengthen documentation quality, clinical accuracy, and professional accountability. Highlights: Simulation-based training strengthened knowledge and skills in nursing documentation Competency improvements were significant only among nurses receiving simulation training Findings support adoption of simulation learning in primary healthcare training programs Keywords: Simulation Based Training, Nursing Documentation, Clinical Competency, Community Health Centers, Nurse Education